How do participants collaborate during an online hackathon? An empirical, quantitative study of communication traces - Schulten, Cleo; Nolte, Alexander; Spikol, Daniel; Chounta, Irene-Angelica (Frontiers in Computer Science, 2022)
Starting as niche programming events, hackathons have since become a popular form of collaboration. Events are organized in various domains across the globe, aiming to foster innovation and learning, create and expand communities and tackle civic and environmental issues. While research around such events has grown in recent years, most studies are based on observations of a few individuals during an event and on post-hoc interviews during which participants report their experiences. Such studies are helpful but somewhat limited in that they do not allow us to study how individuals communicate at scale using technology. To address this gap, we conducted an archival analysis of communication traces of teams during a 48-hour event. Our findings indicate that teams scaffold their communication around the design of an event, influenced by milestones set by the organizers. The officially selected communication platform's main use was to organize the event and the teams and to facilitate contact between participants and hackathon officials. We further investigated the balance of intra-team communication on the given platform and the potential use of additional communication tools.